2020
DOI: 10.21203/rs.3.rs-45999/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Measles Incidence Rates Using Machine Learning and Time Series Methods in the Center of Iran; 1997-2020

Abstract: Background: Measles is a feverish condition labeled among the most infectious viral illnesses in the globe. Despite the presence of a secure, accessible, affordable and efficient vaccine, measles continues to be a worldwide concern. Methods: This study uses machine learning and time series methods to assess factors that placed people at a higher risk of measles. This historical cohort study contained the Measles incidence in Markazi Province, the center of Iran, from April 1997 to February 2020. Logistic regre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In contrast, the false-positive and false-negative rates were 5.80 % and 5.10 %, respectively. To evaluate influencing factors that place individuals at a higher risk of measles [22] utilized ML techniques and found that contact with measles patients, age, rhinorrhea, vaccination, male sex, cough, conjunctivitis, ethnicity, and fever were the crucial factors that were associated with measles disease. The authors in [23] adopted the LASSO (Least Absolute Shrinkage and Selection Operator) logistic regression model on the electronic health record to identify message vaccine-resistant families and obtained 72.0 % precision.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the false-positive and false-negative rates were 5.80 % and 5.10 %, respectively. To evaluate influencing factors that place individuals at a higher risk of measles [22] utilized ML techniques and found that contact with measles patients, age, rhinorrhea, vaccination, male sex, cough, conjunctivitis, ethnicity, and fever were the crucial factors that were associated with measles disease. The authors in [23] adopted the LASSO (Least Absolute Shrinkage and Selection Operator) logistic regression model on the electronic health record to identify message vaccine-resistant families and obtained 72.0 % precision.…”
Section: Introductionmentioning
confidence: 99%